(3fgGjI GdEOQGc aj CSQGQ Ydhe GdCadGcs - (3eMeO Hf CHj HcQ GdaGQSjs
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3aEf Gddg JYGdi deG CaGV Ydi HaVdg hTQafi HNOeg GdebGe GdCYXe s
(3BNQgG (B:s
(3Ch jNQL ef Pdc GdHQL GdPi gh ajg hGddg Gdehab hdJLYd gPG efJgi bhdfG s
(3hefg fSNI KGfjI (B: 192 (3ejbGJ ZjQ cGedI ai (B41 (3bs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B474 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B107 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs